AdaFuse: Adaptive Multiview Fusion for Accurate Human Pose Estimation in the Wild - Zhang, Zhe; Wang, Chunyu; Qiu, Weichao; Qin, Wenhu; Zeng, Wenjun (International Journal of Computer Vision (to appear), 2020)
.